Locke & key. [Vol. 2], Head games - Hill, Joe (Locke & Key, 2011)
Following a shocking death, Kinsey and Tyler Locke turn to their new friend, Zack Wells, for support, little suspecting Zack's dark secret. Meanwhile, six-year-old Bode Locke tries to puzzle out the secret of the head key, and Uncle Duncan is jarred into the past by a disturbingly familiar face.